Male breast cancer in a Hispanic population sample. Descriptive study - Bonilla-Sepúlveda , Óscar Alejandro (2021)
INTRODUCTION: Breast cancer in men is a rare disease, accounting for only 0.2 - 1.5% of all malignant tumors in men. OBJECTIVE: To describe the sociodemographic data, clinical and paraclinical manifestations, treatment, and recurrence in a sample of patients diagnosed with male breast cancer at a private institution. METHODS: Descriptive, retrospective study of an institutional database, in the period 1 January 2017 to 31 December 2020. Demographic, clinical and paraclinical data were collected from the medical records and analyzed using descriptive statistics. RESULTS: The prevalence of breast cancer in men in the sample was 0.44%, median age 73 years. The most frequent symptom was breast mass (n = 5; 100%), median tumor size 2.5 cm (range 1.6 to 5 cm) and ductal histological type (n = 5; 100%). All 5 cases had hormone receptor expression, without HER2 overexpression; stage was locally advanced in 60% (n = 3) (stage IIB-IIIA / B) and metastatic in one case. Mastectomy was performed in 80% of cases (n = 4). The median follow-up was 23 months and relapse was found in 20% (n = 1), with an average time to relapse of 184 months. CONCLUSIONS: In the sample studied, breast cancer in men presented in the seventh decade of life as advanced stage mass, with high hormonal sensitivity. Mastectomy was the main treatment, and most required chemotherapy.